3-Dimensional Dense Coverage: Opportunities and Challenges for Future Mobile Communications - Wei Chen; Dongming Wang; Jiaheng Wang; Feifei Gao; Muheng Peng (Dianxin kexue)
Within just a few decades, mobile communications have undergone a rapid growth from its initial concept to the worldwide prosperity, and essentially changed people's daily life as well as the way of working and thinking, thereby becoming the most important connection between individuals and information networks. Although almost all the spectrum resources have been devoted to mobile communications, the demand of higher capacity over a unit area is still increasing, due to the trend that the density of mobile users is increasing and the amount of traffics grow explosively. No doubt such an ever-increasing demand cannot be met by simply relying on the improvement of either physical layer transmission techniques or planar cellular infrastructures. As an emerging network architecture aiming to future metropolitan patterns, 3-deminsional dense coverage is expected to provide a novel spectrum reuse methodology, significantly improving the spectrum efficiency of mobile communication systems through spectrum reuse in the third dimension beyond the planar dimensions. Some fundamental problems of 3-deminsional dense coverage oriented mobile communications systems were investigated, the key challenges was pointed out, and possible solutions for 3-deminsional networks from both the physical and logical perspectives were provided.